Strengthening Food Safety in Guyana’s Rice Industry: A Supply Chain Review of the Physical Hazards of Rice - Singh, Narita; Singh, Dharamdeo; Persaud, Bissessar; Charles, Bibi Ally; Van-Veen, Davon; Persaud, Rajendra (Discoveries in Agriculture and Food Sciences, 2025)
Rice contributes significantly to Guyana’s economy and plays an important role in ensuring food security. However, within the rice sector, food safety receives less attention compared to productivity and grain quality. This review examines the physical hazards that have the potential to contaminate rice. It focuses on the types, sources, risks and mitigations strategies for the physical hazards identified. Physical hazards are characterized as any unintended foreign or extraneous materials found in food, which may cause harm, illness, injury or psychological trauma to consumers, and can enter rice at multiple points from farm to fork. Inadequate infrastructure, poor hygienic practices, lack of stakeholders’ commitment and weak compliance with food safety measures contribute to an elevated risk of contamination. The paper identifies critical weaknesses in Guyana’s legal framework by analyzing the Rice Factories Act and the Guyana Rice Development Board Act, which together govern key aspects of the rice sector, with minimal focus on food safety. These legal gaps exacerbate poor stakeholder compliance and accountability. Recommendations to effectively prevent and control physical hazards in rice include the implementation of prerequisites programs and food safety systems such as Hazard Analysis Critical Control Points (HACCP). This paper is the first to address the issue of physical hazards in rice in Guyana, it provides a better understanding of the risks of contamination and proposes a foundation for future policy and research efforts tailored to the country’s rice supply chain.